Analysis of the Effect of Liquidity Ratios, Solvency and Activity on the Financial Performance of the Company (Literature Review of Corporate Financial Management) - Medeline Effendie, Jessica; Henny A. Manafe; Stanis Man (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This article reviews the influence that aims to really know about liquidity ratios, slovability, and activities that affect the company's financial performance. Liquidity is proxied by current ratio (CR), solvability is proxied by debt to equity ratio (DER), activity is proxied by inventory turnover (InvTO) and total asset turn over (TATO), while the company's financial performance is proxied by return on equity (ROE). This article was written in order to determine the hypothesis of the influence between variables that can be used in subsequent research. The results of the library research are: 1) Current ratio (CR) separately affects return on equity (ROE); 2) Debt to equity ratio (DER) has a separate impact on return on equity (ROE); 3) Inventory turn over (InvTO) has a separate effect on return on equity (ROE); 4) Total asset turn over (TATO) has a partial impact on return on equity (ROE); 5) CR, DER, InvTO, TATO simultaneously have a positive effect on ROE.